Control Method for PEMFC Using Improved Deep Deterministic Policy Gradient Algorithm - Li, Jiawen; Li, Yaping; Yu, Tao (Frontiers in Energy Research, 2021)
A data-driven PEMFC output voltage control method is proposed. Moreover, an Improved deep deterministic policy gradient algorithm is proposed for this method. The algorithm introduces three techniques: Clipped multiple Q-learning, policy delay update, and policy smoothing to improve the robustness of the control policy. In this algorithm, the hydrogen controller is treated as an agent, which is pre-trained to fully interact with the environment and obtain the optimal control policy. The effectiveness of the proposed algorithm is demonstrated experimentally.